Qualitative Research as an Area to Co-existence and Co-creation of the Subjects of Research - Pupils and Teachers. From a Teacher Filled with the Spirit of Research Through Living Laboratories to the Creative Research and the Research that Creates - Magdalena Ciechowska (Nicolaus Copernicus University in Toruń, 2020)
These aspects are not widely discussed in the methodological literature, meanwhile they are important for the emergence of synergy - a characteristic feature of qualitative research. The article also points to concepts that are important for the co-existence and co-creation of the research subjects - concepts of John McKernan that concern the teaching research in action and Living Laboratories, and creative research. The author's concept is also presented - research that creates, whose special feature is the co-existence and co-creation of research subjects. Those aspects of qualitative research should be highlighted in wide seeing at teacher research in their own daily practice. In this job, all is the research - meeting the student, evaluation, improving teaching methods, etc.